The Effect of Brand Credibility and Customer Loyalty on Iphone Smart Phone Brand Image - Silcyljeova Moniharapon; Lucky O.H. Dotulong; Paulina Van Rate; Ferdy Roring; Mirah H.Rogi; Indrie Debbie Palandeng (Universitas Dharma Wacana, 2022)
This study aims to analyze the relationship between brand credibility variables, customer loyalty to the brand image of Iphone smartphone users. This study involved 40 respondents from students of the Faculty of Economics, Sam Ratulangi University, the data collection method used a questionnaire and the data analysis method used a multiple regression analysis approach which was then processed using SPSS. The results of this study state that brand credibility and customer loyalty have a positive and significant effect on brand image. Based on the results of the research that has been done, suggestions are made, including the following: (1) Researchers suggest that future research expand the object of research so that the results can be generalized better than previous research. (2) Then, the company must also improve its brand image, and must pay attention to brand credibility and customer loyalty, because it is proven that greater brand credibility accompanied by existing customer loyalty will improve the existing brand image. This is an opportunity for the company to support the company's success in the future.